Kajian Keselamatan dan Kesehatan Kerja ( K3 ) Konstruksi Balok Pada Konstruksi Bangunan Gedung - Hendra Alexander; Silvia Nengsih; Oni Guspari (Jurnal Ilmiah Poli Rekayasa, 2019)
Construction projects have a very high risk of work accidents. Work accidents will disrupt all project activities that can cause death and loss to the project. A work accident is an undesirable and unexpected incident which could result in loss of life and property. Based on Law No.1 of 1970 concerning work safety, work accident is an unexpected and undesirable event that disrupts the regulated process of an activity and can cause harm to both human victims and property. For this reason, it is necessary to have a construction safety management system using methods Hazard Identification Risk Determining Control (HIRADC). HIRADC will be implemented if there is support from management for occupational safety and health (OSH) in the form of policies, organizational structure and budget. From the studies conducted, the most common hazards are falling, punctured, scratched, tripped, bumped, inhaled dust, electric shock, exposed to concrete splashes with extreme risk of risk of injury, disability and even death. For this reason, there is a need for handling control in the form of mandating the use of PPE, administrative control such as making work instructions, SOP, must have SIO and SILO, installing signs, and doing engineering such as work methods, shopdrawing, providing regular training.